Use of synchrotron medical microbeam irradiation to investigate radiation-induced bystander and abscopal effects in vivo. Issue 6 (September 2015) - Fernandez-Palomo, Cristian; Bräuer-Krisch, Elke; Laissue, Jean; Vukmirovic, Dusan; Blattmann, Hans; Seymour, Colin; Schültke, Elisabeth; Mothersill, Carmel
Abstract The question of whether bystander and abscopal effects are the same is unclear. Our experimental system enables us to address this question by allowing irradiated organisms to partner with unexposed individuals. Organs from both animals and appropriate sham and scatter dose controls are tested for expression of several endpoints such as calcium flux, role of 5HT, reporter assay cell death and proteomic profile. The results show that membrane related functions of calcium and 5HT are critical for true bystander effect expression. Our original inter-animal experiments used fish species whole body irradiated with low doses of X-rays, which prevented us from addressing the abscopal effect question. Data which are much more relevant in radiotherapy are now available for rats which received high dose local irradiation to the implanted right brain glioma. The data were generated using quasi-parallel microbeams at the biomedical beamline at the European Synchrotron Radiation Facility in Grenoble France. This means we can directly compare abscopal and "true" bystander effects in a rodent tumour model. Analysis of right brain hemisphere, left brain and urinary bladder in the directly irradiated animals and their unirradiated partners strongly suggests that bystander effects (in partner animals) are not the same as abscopal effects (in the irradiated animal). Furthermore, the presence of a tumour in the right brain alters the magnitude of both abscopal and bystander effects in the tissues from the directly irradiated animal and in the unirradiated partners which did not contain tumours, meaning the type of signal was different.